2022
DOI: 10.1111/opn.12451
|View full text |Cite
|
Sign up to set email alerts
|

Relatives’ experiences of the hospitalisation of older people with COVID‐19: A qualitative interview study

Abstract: Background During the COVID‐19 pandemic, visitors were restricted from hospitals, separating them from hospitalised friends and family to reduce the infection risk. Objectives The objective was to explore how relatives of older people acutely admitted to hospital with COVID‐19 experienced being a relative, and how they felt about their contact with health care professionals (HCPs) when visitor restrictions prevented their physical presence in the ward. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The residents all had access and support to engage in virtual visits; however, they were not overly interested in virtual visits, some claiming the technology was too complicated. Hoffman et al [ 25 ] and Giebel et al [ 26 ] similarly found that older people sometimes found the mobile technology too complex to use. Rather, it was mostly families who communicated the need for virtual visits, reporting the challenges they experienced depending on the availability of staff or who was on duty that day.…”
Section: Discussionmentioning
confidence: 99%
“…The residents all had access and support to engage in virtual visits; however, they were not overly interested in virtual visits, some claiming the technology was too complicated. Hoffman et al [ 25 ] and Giebel et al [ 26 ] similarly found that older people sometimes found the mobile technology too complex to use. Rather, it was mostly families who communicated the need for virtual visits, reporting the challenges they experienced depending on the availability of staff or who was on duty that day.…”
Section: Discussionmentioning
confidence: 99%
“…Data were anonymised to ensure participant anonymity and respect good research practice in this type of study, as per the Declaration of Helsinki (35). Data from the self-reported questionnaires returned were extracted into an Excel© spreadsheet (Microsoft, Redmond, Washington, USA), cleaned, and imported into IBM SPSS® software, version 28 (IBM Corp, Armonk, New York, USA), for analyses.…”
Section: Data Analysesmentioning
confidence: 99%
“…This was linked to not being able to see how their loved one was being cared for and having to put their trust in healthcare institutions (35). Unclear information or inconsistencies in institutional policy contributed to these uncertainties and relatives sought e cient face-toface communication (35). Hoffman et al highlighted the need for personal attention from relatives (35)(36)(37).…”
Section: Introduction -Backgroundmentioning
confidence: 99%
See 2 more Smart Citations